2018
DOI: 10.4172/2157-2518.1000319
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pre- and Post-translational Expressions of COXIV-1 and MT-ATPase 6 Genes in Colorectal Adenoma-Carcinoma Tissues [NIH-NIGMS]

Abstract: Objective: Colorectal cancer (CRC) develops from precancerous adenomatous polyps to malignant lesions of adenocarcinoma. Elucidating inhibition mechanisms for this route in patients with a risk of developing CRC is highly important for a potential diagnostic or prognostic marker. Differential expression of nuclear-encoded cytochrome c oxidase subunit 4 (COXIV) seems to contribute to a more unregulated respiration due to loss of ATP inhibition. Majority of energy for tumor transformations are mitochondrial orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…Hence, elucidating the crosstalk mechanism between the nuclear and mitochondrial genome regarding the functional impacts of miRNAs in tumor progressive stages and possible ROS productions, (as shown in Figure 6), will pivotally aid in the clinicopathological characteristics of CRC. Our lab had reported a decreased in mitochondrial isolated COXIV-1 a nuclear encoded subunit of complex IV with the progressive stages of CRC adenomas [43]. This finding was strikingly important given the role of COXIV-1 in regulating of the mitochondrial encoded subunits of complexes IV and V, as well as regulation of oxidative phosphorylation.…”
Section: Discussionmentioning
confidence: 83%
“…Hence, elucidating the crosstalk mechanism between the nuclear and mitochondrial genome regarding the functional impacts of miRNAs in tumor progressive stages and possible ROS productions, (as shown in Figure 6), will pivotally aid in the clinicopathological characteristics of CRC. Our lab had reported a decreased in mitochondrial isolated COXIV-1 a nuclear encoded subunit of complex IV with the progressive stages of CRC adenomas [43]. This finding was strikingly important given the role of COXIV-1 in regulating of the mitochondrial encoded subunits of complexes IV and V, as well as regulation of oxidative phosphorylation.…”
Section: Discussionmentioning
confidence: 83%
“…In particular, higher levels of TFAM, COX-II, ND6 (NADH dehydrogenase subunit 6), and COX IV were detected in cancer in comparison to primary colon cells [ 62 ]. Similarly, a comparison of the mRNA levels of COX IV-1 and ATPase6 from patients with different stages of CRC have found that the decreased expression of COX IV-1 and ATPase6 correlates with increased ROS production during colorectal adenomatous polyp progression, thus pointing to the central role of COX IV-1 in the colorectal cell’s mitochondria energy production as they progress from polyps to carcinoma [ 63 ]. Other research has also confirmed higher and gender-specific expression of COX-II [ 64 ] and tumour grade-dependent of COX I [ 65 ].…”
Section: Associated Mitochondrial Mutations and Dysfunctionsmentioning
confidence: 99%
“…COX IV (Cytochrome c oxidase subunit 4)белок, который является одной из полипептидных цепей цитохромоксидазы, участвует в переносе электронов в митохондриях. Принадлежит к семейству оксидазы IV цитохрома c. Характеризует эффективность цепи тканевого дыхания [19,31].…”
Section: маркеры нарушений энергетической функции митохондрийunclassified